Health and human rights in Europe - Toebes, Brigit C. A.; Hartlev, Mette; Hendriks, Aart; Herrmann, Janne Rothmar (Cambridge, United Kingdom ; Antwerp ; Portland, OR : Intersentia, 2012)
"The area of 'health and human rights' is a new and emerging field of law. Taking a 'health and human rights approach' means using international, European and national human rights law in relation to a wide range of health issues, including access to health care, health data protection, the quality of pharmaceutical drugs, as well as medical-ethical issues such as abortion and euthanasia. There is, however, still very little understanding of the various and multiple legal interfaces between 'health' and 'human rights', and of the implications of this approach for legal research and practice. To fill this gap, this volume seeks to outline the legal content and implications of this new area of the law. Its focus is on Europe, as the European context raises specific questions, not only from a legal and a political perspective, but also in terms of health issues and health outcomes. The book first discusses how the European institutions (the Council of Europe and the European Union) deal with health and human rights. Subsequently, it describes the meaning of the most important human rights involved in this area, and it addresses a variety of themes and approaches that engage with health and human rights links, including patient rights, reproductive health, and issues surrounding death and dying. Lastly, it discusses the position of a number of vulnerable groups, in particular, disabled persons, the elderly, and children"--Page 4 of cover.
The Council of Europe and health and human rights / Aart Hendriks -- The European Union and health and human rights / Janne Rothmar Herrmann and Brigit Toebes -- The right to health and other health-related rights / Brigit Toebes -- Patients' rights / Mette Hartlev -- Reproductive health / Janne Rothmar Herrmann -- Euthanasia and physician-assisted suicide from a human rights standpoint / Jozef Dorscheidt -- Health inequalities and the social determinants of health / Brigit Toebes, Aart Hendriks, and Karien Stronks -- Children and the right to health protection / Henriette Sinding Aasen -- The rights of persons with disabilities in the context of healthcare / Oddny Mjoll Arnardottir -- The right to health protection for the elderly : key elements and state obligations / Henriette Sinding Aasen.
Includes bibliographical references.
Keywords: Europarat; Europa; Human rights -- Europe; Right to health -- Europe; Health services accessibility -- Law and legislation -- Europe; Medical care -- Law and legislation -- Europe; Health education -- Europe; Human Rights; Delivery of Health Care; Health Services Accessibility; Health Status Disparities; Health education; Health services accessibility -- Law and legislation; Human rights; Medical care -- Law and legislation; Right to health; Gesundheitsrecht; Menschenrecht; Gesundheitswesen; Medizin; Menschenrecht; Human rights -- Europe; Right to health -- Europe; Health services accessibility -- Law and legislation -- Europe; Medical care -- Law and legislation -- Europe; Health education -- Europe; 2; 2; HEALTH; HUMAN RIGHTS; LAWS AND REGULATIONS; RIGHT TO HEALTH; LEGAL ASPECTS; EUROPE; Europe; Europe; 2